Motionera Mera A cross-platform application for physical exercise - Eriksson, Sebastian; Käkelä, Aki; McNabb, Eric; Yeh, Alexander (My University, 2014)
The City of Gothenburg wanted an application for their current campaign promoting physical exercise for the citizens of Gothenburg. The work consists of digitizing their current card system where users make marks on the card when they exercise. This report discusses the various aspects of adapting the application for both mobile and desktop devices, as well as the server components required to manage the campaign and user data. The result is an application primarily built with web technologies, which makes it compatible with any device that has a web browser, including smartphones, tablets, desktops, and TVs. The discussion comprises the user interface and di erences in the mobile and desktop platforms, primarily relating to Android and iOS on the mobile side. The discussion also involves security and privacy in the client-server communication.
Keywords: Data- och informationsvetenskap; Computer and Information Science